Sexuality of Female Spina Bifida Patients: Predictors of a Satisfactory Sexual Function - Guilherme Lang Motta; Anna Bujons; Yesica Quiróz; Erika Llorens; Maira Zancan; Tiago Elias Rosito (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To assess the sexual function of women with spina bifida (SB), and to verify the factors that influence their sexual function. Methods A cross-sectional study in which a validated female-specific questionnaire was applied to 140 SB female patients from four different cities (Porto Alegre, Brazil; and Barcelona, Madrid, and Málaga, Spain) between 2019 and 2020. The questionnaires collected data on the clinical characteristics of SB, and female sexual function was assessed using the 6-item version of the Female Sexual Function Index (FSFI-6) validated to Portuguese and Spanish. Results Half of the patients had had sexual activity at least once in the life, but most (57.1%) did not use any contraception method. Sexual dysfunction was present in most (84.3%) patients, and all sexual function domains were impaired compared those of non-neurogenic women. The presence of urinary and fecal incontinence significantly affected the quality of their sexual activity based on the FSFI-6. Conclusion The specific clinical aspects of the SB patients, such as urinary and fecal incontinence, should be properly addressed by their doctors, since they are associated with reduced sexual activity and lower FSFI-6 scores in the overall or specific domains. There is also a need to improve gynecological care among sexually-active SB patients, since most do not use any contraceptive methods and are at risk of inadvertent pregnancy.